Educational escape room as a gamification strategy for improving oral skills in the English language - Suntaxi Llumiquinga, Jonathan (2022)
Modern education tends to be more flexible and with a variety of strategies that permit learners to develop and propel their language skills. In this regard, the implementation of educational escape rooms are necessary to be accord with these days’ demands. The present study aims to identify the functionality and applicability of some games in schools and in different settings that support the improvement of the students’ communicative skills. In this way, a mixed-method with a control and experimental group that includes qualitative and quantitative data, observation and a survey permit to understand the students´ needs and their perceptions regarding the use of games to enhance their language skills. In addition, it shows the importance to relate and match accurately the language topics with specific games. The most important results show that students are eager to learn by playing and the significance of working in different environments that permit students to change their traditional learning. It is also essential to include that even though traditional games are appealing for young learners, the use of technology and internet connection turned into a powerful tool of motivation and engagement for students. As a conclusion, it was evidenced that modifying the teaching way produces high commitment among students and their curiosity influences to develop positive interaction and communicative skills.